KEANEKARAGAMAN JENIS BURUNG RANGKONG (Bucerotidae) DI STASIUN PENELITIAN WAY CANGUK TAMAN NASIONAL BUKIT BARISAN SELATAN - muhammad sarpin pratama; agus setiawan; sugeng prayitno harianto; nuning nurcahyani (Jurnal Belantara, 2021)
The rise of hornbill hunting and deforestation that occurred in Indonesia, especially the island of Sumatra lately, threatening the preservation of these birds in nature. The purpose of this study was to determine thediversity of hornbill species in the Way Canguk Research Station, Bukit Barisan Selatan National Park. The method used in this study is a transect line with a total of 18 line transects. The data obtained was processed using the Shanon wienners diversity index formula, then translated with descriptive analysis. A total of 5 types of hornbills found in these locations are rhinoceros hornbills (Buceros rhinoceros), helmeted hornbills (Rhinoplax vigil), wreathed hornbill (Rhyticeros undulatus), bushy crested hornbill (Anorrhinus galeritus) and white crowned hornbill (Berenicornis comatus), with a species diversity index value of 1.00 included in the low category and the evenness of the species is a stable with an evenness index value of 0.62. The highest abundance of hornbills is (Anorrhinus galeritus) a beside that hornbills can be found in almost all transect lines.